EFFECTIVENESS OF THE INDEPENDENT ENTREPRENEURSHIP PROGRAM ON IMPROVING STUDENTS' MINDSET, SOFT SKILLS, AND HARD SKILLS - Ulil Amri; Jasri Jasri; Roslinda Roslinda; Rafiqa Hatharita (Universitas Muhammadiyah Metro, 2026)
ABSTRACT The implementation of entrepreneurship programs in higher education is increasingly important as universities are expected to produce graduates who are not only academically competent but also adaptive, innovative, and capable of creating business opportunities. However, the effectiveness of the Independent Entrepreneurship Program in improving students’ entrepreneurial competencies has not been widely evaluated at the institutional level. This study aimed to examine the effectiveness of the Independent Entrepreneurship Program in improving students’ entrepreneurial mindset, soft skills, and hard skills at Universitas Muhammadiyah Makassar. A quantitative approach was employed using linear regression analysis involving 90 students who participated in the program. The results showed that the Independent Entrepreneurship Program had a significant effect on entrepreneurial mindset (regression coefficient = 0.669; p = 0.000), soft skills (regression coefficient = 0.632; p = 0.000), and hard skills (regression coefficient = 0.770; p = 0.000). These findings indicate that students’ direct involvement in entrepreneurial activities contributes positively to the development of entrepreneurial attitudes, interpersonal and managerial abilities, and technical business skills. This study contributes to the literature on entrepreneurship education by providing empirical evidence that experiential learning-based entrepreneurship programs can strengthen multidimensional entrepreneurial competence in higher education. Practically, the findings offer recommendations for universities to improve the design and implementation of entrepreneurship programs that are more relevant to students’ future career and business challenges. Keywords: hard skill; entrepreneurship; mindset; soft skills; independent entrepreneurs ABSTRAK Pelaksanaan program kewirausahaan di perguruan tinggi menjadi semakin penting karena perguruan tinggi dituntut menghasilkan lulusan yang tidak hanya unggul secara akademik, tetapi juga adaptif, inovatif, dan mampu menciptakan peluang usaha. Namun demikian, efektivitas Program Wirausaha Merdeka dalam meningkatkan kompetensi kewirausahaan mahasiswa masih belum banyak dievaluasi pada tingkat institusi. Penelitian ini bertujuan untuk menganalisis efektivitas Program Wirausaha Merdeka dalam meningkatkan entrepreneurial mindset, soft skills, dan hard skills mahasiswa Universitas Muhammadiyah Makassar. Penelitian ini menggunakan pendekatan kuantitatif dengan analisis regresi linier terhadap 90 mahasiswa peserta program. Hasil penelitian menunjukkan bahwa Program Wirausaha Merdeka berpengaruh signifikan terhadap entrepreneurial mindset (koefisien regresi = 0,669; p = 0,000), soft skills (koefisien regresi = 0,632; p = 0,000), dan hard skills (koefisien regresi = 0,770; p = 0,000). Temuan ini menunjukkan bahwa keterlibatan langsung mahasiswa dalam aktivitas kewirausahaan berkontribusi positif terhadap pengembangan pola pikir kewirausahaan, kemampuan interpersonal dan manajerial, serta keterampilan teknis bisnis. Penelitian ini berkontribusi pada pengembangan kajian pendidikan kewirausahaan dengan menghadirkan bukti empiris bahwa program kewirausahaan berbasis experiential learning mampu memperkuat kompetensi kewirausahaan multidimensi di perguruan tinggi. Secara praktis, hasil penelitian ini dapat menjadi dasar bagi perguruan tinggi dalam menyempurnakan desain dan implementasi program kewirausahaan yang lebih relevan dengan tantangan karier dan dunia usaha masa depan. Kata Kunci:​ hard skill; kewirausahaan; mindset; soft skill; wirausaha merdeka